Development of discovery learning-based student worksheets to facilitate critical thinking skills in phase D students - Hafshoh; Suanto, Elfis; Armis (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
The aim of this development research is to design discovery learning-based student worksheets (LKPD) to facilitate the mathematical critical thinking skills of Phase D students by meeting validity and practicality criteria. This study is motivated by the crucial role of critical thinking skills in students' education. The research employs a development method (R&D) following the 4-D model (define, design, develop, and disseminate). The study involved 15 students from Babussalam Junior High School, Pekanbaru, as the test subjects. Research instruments included a validation questionnaire to assess the validity of the LKPD and a student response questionnaire to evaluate its practicality. Based on the expert validator's analysis, the validity score was 94.43%, indicating the LKPD is highly valid. Meanwhile, the practicality score, derived from the student response questionnaire, was 87.98%, categorizing the LKPD as highly practical. Thus, the development of discovery learning-based LKPD is recommended for use in learning activities related to circle content to enhance the critical thinking skills of Phase D students.